Factors that influence Consumer Buying Decision on Contact Lens in Malaysia - et. al., Alex Hou Hong Ng, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Malaysian contact lenses and market size is growing steadily over the last few years. In this context, this study aims to examine the factors that affect the consumer buying decision on Contact Lens in Malaysia. This research explores the expansion of costs, labels, product efficiency and recommendations for contact lenses in Malaysia. A questionnaire-based survey method was employed to gather the data from 417 respondents in Malaysia and the data was analyzed using SPSS. The findings revealed that price, brand, product efficiency and advice had a positive effect on customer buying behavior. The findings of this study offer a better explanation of how to implement competitive plans for customer experience and client satisfaction to the marketer of contact lens companies. It is advised that contact lens producers may need to go through a sequence of R&Ds to create contact lens features that will support customers' everyday lives and represent product success in their advertising and promotion strategies.